Korelasi Kelimpahan Crown of Thorns Starfish (Acanthaster planci) dengan Tutupan Karang Hidup di Perairan Singaraja, Buleleng, Bali - Tanzil, Anjani; Giri Putra, I Nyoman; Pratama Atmaja, Putu Satya (Journal of Marine Research and Technology, 2024)
Ganesha Beach and Celuk Agung Beach, located in the waters of Singaraja, Bali Island, have resources for coral reefs. Previous studies showed that the corals in these waters were in moderate conditions, and The Crown of Thorns Starfish (Acanthaster planci) were found in these waters. These starfish are corallivores, meaning they eat corals. This research aimed to calculate the abundance of A. planci and coral reef cover percentage and determine the correlation. This research used the Benthos Belt Transect method to calculate the abundance of A. planci; the collected data includes the number of A. planci found, color, and type of substrate where it was found. Point Intercept Transect was used to calculate the coral reef cover percentage, and the correlations were accessed using Pearson Correlation. The area of the research is 100 m 2 and has two stations. This study showed that the lowest abundance of A. planci was at station 2 at 0.004 and/m 2 (normal conditions), and the highest was at 0.018 and/m 2 (concerning conditions). The coral cover percentage in the research area is moderate, with the highest coral cover alive at station 1 (41%) and the lowest in station 2 (31%). The correlation between the density of A. planci and the living coral cover showed negative values, which indicates that the increasing number of A. planci will decrease the living coral cover.